Development and Validation of an Empirical Instrument to Measure Organizational and Institutional Functioning Capacity Within International Extension Networks - Kevan W Lamm; Alexa Lamm; Kristin E Davis; Catherine Sanders; Alyssa Powell (Journal of International Agricultural and Extension Education, 2022)
International extension networks provide vital services to stakeholders using a variety of organizational structures. To continue offering services desired by stakeholders, it is important that both public and private extension networks develop effective organizational functioning capacities. Despite this need, an instrument to empirically examine the perceived capacities of effective international extension network organizational and institutional functioning was unavailable in the literature. The present study developed and validated the International Extension Network Organizational Functioning (IENOF) scale. Scale development included validation of content, response process, internal structure, and consequential utility. Structural analysis indicated the 21-items loaded on four factors, including: network structure and relevance, network management and activities, network strategy and guidance, and network leadership. The results of the study indicate the IENOF may provide an empirical instrument to examine the capacities of international extension network organizational functioning. Furthermore, the analysis provides insights into the nuance and unique characteristics associated with international extension network organizations. Replication studies and further statistical analyses are recommended to examine the nature of the instrument and associated outcome variables of interest. From a practical perspective the IENOF is recommended to be considered as an input to the theory of co-innovation to aid international extension networks in fostering a culture of innovation. Utilizing IENOF insights to inform the theory of co-innovation should better enable extension networks to provide services and programming that meet the needs of network stakeholders.
Keywords: organizational functioning; international extension; co-innovation; scale development; rural advisory services; capacity assessment